Epithelioid Hemangioma (Angiolymphoid Hyperplasia With Eosinophilia) of the Heart With Peripheral Eosinophilia and Nephrotic Syndrome. (February 2016) - Machado, Isidro; Chong, Agustín; Serrano, Anisia; Naranjo Ugalde, Alfredo Mario; Pineda, Damian; Savón, Laynes; Olivera, Ever; Llombart-Bosch, Antonio
Epithelioid hemangioma (EH) is a rare benign vascular lesion, characterized by endothelial cells with epithelioid/histiocytoid appearance. Heart involvement is extremely rare. We present an unusual case of cardiac EH in a young woman with supraventricular arrhythmia, nephrotic syndrome (membranous glomerulopathy), and peripheral eosinophilia after a pregnancy and normal partum resembling Kimura disease. Echocardiogram showed a large tumor mass in the right cardiac ventricle. The cardiac tumor was removed and the histopathology revealed an endothelial proliferation associated with abundant eosinophils. The neoplastic endothelial cells were eosinophilic and polygonal with epithelioid/histiocytoid morphology. Lymphoid nodules were occasionally seen. The neoplastic cells were positive for CD34, CD31, ERG, and factor VIII and negative for CK. A diagnosis of EH was rendered. The patient was alive and well after surgical resection. EH and Kimura disease represent separate entities, but clinical and/or histological overlapping can be observed. Epithelioid/histiocytoid endothelial cells constitute the hallmark feature that favors a final diagnosis of EH.